Laparoscopic Surgery for Rectal Cancer - Indar, Adrian (The Permanente Journal, 2009)
Laparoscopic surgery for rectal cancer is much more challenging than that for colon cancer because of the confined space within the pelvis. Further, because of the tumor's location in the pelvis, maintenance of resection margins is of greater concern. Nonrandomized studies by groups experienced in laparoscopic surgery have shown both that it produces short-term outcomes equivalent to those for open surgery and that it can be performed safely from an oncologic perspective. Nonsurgical complications appear to be fewer, but conversion to open surgery may become a real issue. This review summarizes these findings by addressing technical considerations, early outcomes, late outcomes, costs, and complications.